CASE REPORT MYOCARDITIS IN UNIDENTIFIED SNAKE BITE - Tsani Fauzi Elpani; Yandi Arifudin (International Medical Journal Corp. Ltd, 2026)
Background : Venomous snakebites are rare, with an estimated 1,000 cases annually, resulting in approximately 5 deaths. Venomous snakebites are a medical emergency that can result in life-threatening clinical effects. Cardiovascular complications in snakebite patients include myocarditis, shock, ventricular dysrhythmias, and cardiac arrest. Myocarditis caused by viper envenomation in humans rarely happens, but it could be dangerous if not detected and treated early. Case Illustration: In the afternoon, a 74-year-old man made a fuss scene of a snake bite on his left leg, which happened in a rice field. The shape of the snake cannot be identified. The sense of the leg becoming increasingly swollen and turning purple. Additional complaints were shortness of breath (+). Risk factors were uncontrolled hypertension and smoking regularly, one pack a day. The bites are showing fang marks (+), swelling (+), and edema (+). On the second day, the bruises from the bite had spread. Supporting examinations revealed leukocytosis, increased troponin I, an ECG recording showed ischemia in the inferior and anterolateral regions, and a PA chest X-ray showed cardiomegaly. Echocardiography results showed hypokinetic inferior septal, mitral regurgitation, tricuspid regurgitation, aortic regurgitation, and LVEF 37%. The treatment provided included immobilization of the bite site with a splint, administration of SABU, cefotiam, spironolactone, ramipril, and furosemide. Conclusion : Venomous snakebites can cause adverse cardiovascular events. One of the complications, myocarditis, occurs as a direct result of the venom's toxins, which can damage myocardial cells.